Peran Guru PAI dalam Mengaktualisasikan Nilai Aswaja di MA NU Assalafie Babakan Ciwaringin Cirebon - Tuti Alawiyah; Tosuerdi Tosuerdi; Imam Musyaffa (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research focuses on the role of Islamic Religious Education (PAI) teachers in actualizing the values of Ahlussunnah Wal Jamaah (Aswaja) Annahdliyah as one of the Islamic guidelines that develop and are firmly rooted in Indonesia. Aswaja values have distinctive characteristics that emphasize moderation, tolerance, and maintaining religious traditions that have been acculturated with local culture without abandoning the principles of Islamic law. In the context of education, Aswaja is an important foundation in shaping the character of students who are religious, nationalist, and able to appreciate diversity in a multicultural society. The purpose of this study is to find out: (1) how to implement the role of PAI teachers in integrating Aswaja values in the learning process at MA NU Assalafie Babakan Ciwaringin Cirebon, (2) problems that arise in the actualization process, such as limited student understanding, differences in family backgrounds, to the challenges of globalization currents that can affect religious understanding, and (3) efforts made by teachers to overcome them, for example, through a personal approach, strengthening Aswaja-based teaching materials, and collaboration with schools and parents. This study uses a qualitative method with a field study approach. Data was obtained through observation, in-depth interviews with madrasah heads, deputy heads of student affairs, and five PAI teachers, and documentation of learning activities. Data analysis was carried out through the stages of reduction, presentation, and conclusion drawn, then tested for validity with the source triangulation technique. The results of the study show that the role of PAI teachers is very crucial in maintaining the value of Aswaja so that it remains relevant and internalized in students.